Relationship between growth and development of rat pups and their head and teeth development - Uzun Saylan, BC; Yılmaz, C; Karakullukcu, S; Yılmaz, O (Journal of the Hellenic Veterinary Medical Society, 2025)
Laboratory rats are indispensable experimental animal models used instead of humans. In translational medicine research, the life period of the animal model must be similar to the human life period in which the research question arose for the validity and applicability of research results. In this study, we aimed to examine the laboratory rats used instead of humans during postnatal lactation, childhood, adolescence, preadolescence, and young adult life periods while also contributing to laboratory animal science. Life periods, which are years for humans, are expressed in days for laboratory rats. Therefore, if researchers do not perform experimental procedures in the animal life period appropriate for the human life period in which the research questions arise, the research results will not be valid, and applicable information cannot be obtained. Because each animal shows anatomical and physiological changes specific to its life period, in laboratory rats, the upper and lower incisors emerge in the first 8-10 days after birth, and the prematüre period is completed. In the 30-day period after birth, laboratory rats complete the lactation period and childhood period and reach a body weight of approximately 12 times their birth body weight. In addition, there was no significant difference between male and female rat pups regarding head length, head width, jaw width, and incisor length/width measurements up to 30 days after birth. In contrast, these measurements were higher in male rat pups than female pups after the 30th day (p<0.05). It was determined that the effects of pubertal physiological changes in male rats began to be seen after 30 days after birth. In connection with this, this situation should be taken into consideration when evaluating and interpreting the effects of experimental procedures in both pediatric animal models and adult rat models.